2023
DOI: 10.3390/pr11030922
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Interaction between the Antiviral Drug Umifenovir and Umifenovir Encapsulated in Phospholipids Micelles (Nanosome/Umifenovir) with dsDNA as a Model for Pharmacogenomic Analysis by Electrochemical Methods

Abstract: In the present study, the electrochemical behavior of antiviral drug umifenovir (Umi) and umifenovir encapsulated in phospholipids micelles (nanosome/umifenovir, NUmi) were investigated for the first time on screen-printed electrodes modified by carbon nanotubes. We have shown that Umi can be electro oxidized around the potential of +0.4 V in the concentration range of 50–500 µM (R2 = 0.992). Non-overlapping signatures of DNA and umifenovir (10–150 µM) permit to register interaction between umifenovir (or umif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Earlier, we showed that electrochemical oxidation of dsDNA was successfully achieved on SPE/CNT after dsDNA immobilization by physical entrapment/absorption on the surface of the modified electrodes. Modification of SPEswith CNT stabilized with carboxymethylcellulose (SPE/CNT) allowed the registering of electrochemical oxidation of guanine, adenine and thymine in the immobilized dsDNA [ 40 , 41 , 71 ]. Adding nanosized titanium (IV) oxide TiO 2 improved the sensitivity of electrodes for the registration of dsDNA ( Figure 4 a,b), as in the case of protein registration [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier, we showed that electrochemical oxidation of dsDNA was successfully achieved on SPE/CNT after dsDNA immobilization by physical entrapment/absorption on the surface of the modified electrodes. Modification of SPEswith CNT stabilized with carboxymethylcellulose (SPE/CNT) allowed the registering of electrochemical oxidation of guanine, adenine and thymine in the immobilized dsDNA [ 40 , 41 , 71 ]. Adding nanosized titanium (IV) oxide TiO 2 improved the sensitivity of electrodes for the registration of dsDNA ( Figure 4 a,b), as in the case of protein registration [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on this observation, we used SPEs only for single measurements. This regimen is typical for the irreversible electrochemical process [ 40 , 41 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this study is to discover the effects of DOX, or DOX as nanoformulated forms (DOX-loaded NPhs and DOX with the NGR targeted peptide), onto DNA as a model molecule in pharmacogenomics. To assess the mechanism of interaction of medications with DNA, we used electrochemical techniques, which possess high sensitivity, selectivity, and registration of a concentration-dependent “response” of heterocyclic nucleobases on drug influence [ 12 , 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%